Moisture sorption isotherms and thermodynamic properties of cowpea (Vigna unguiculate L. Walp) stored in a chamber under controlled humidity and temperature - Karatas, Mukaddes; Arslan, Nurhan (Wiley, 2022)
The sorption process of cowpea stored in a chamber the relative humidity of which is controlled by an atomizing humidifier was studied in 25, 35, and 45 degrees C over 0.1%-0.9% water activities. A type III (J-shapes) behavior was observed for the sorption isotherms of cowpea. The temperature increase caused a decrease in the equilibrium moisture content (EMC). Hysteresis effect existed over the entire water activity range. The experimental sorption data were fitted to many well-known isotherm equations (GAB, BET, Henderson, Oswin, Peleg, Smith, Caurie, Halsey, Ferro-Fontan, Kuhn, Chung-Pfost, White-Eiring). Among models evaluated, the Peleg equation was selected as the model giving the best fit quality for predicting the sorption behavior of cowpea. The sorption isotherms data were used to estimate the thermodynamic functions (sorption isoteric heat and entropy, Gibbs free energy, net integral enthalpy and entropy) providing an understanding energy requirement. The sorption isosteric heat calculated using the Clausius-Clapeyron equation and the net integral enthalpy decreased swiftly with increasing moisture content while an increase was observed in the net integral entropy. Thermodynamic approach showed that the sorption process for cowpea was the enthalpy-controlled and nonspontaneous. Practical Applications Since the determination of the physicochemical relationship between water and food is very important for the continuity of food quality stability, many researches are carried out on this subject. The quality stability of foods is expressed in moisture sorption isotherms, which are the relationship between EMC and water activity at any temperature. Generally, data on equilibrium humidity were obtained using saturated salt solutions. No study was found on the moisture sorption isotherm data of cowpea stored in a chamber whose relative humidity is controlled by an atomized humidification system. It is thought that the data obtained with this system will achieve more successful results in equipment and process design since it is closer to the actual storage conditions.
Keywords: cowpea; food storage; moisture sorption isotherm; thermodynamics